Non-Violent Action to Reform Medical Education in Nepal - The Fasts-unto-death of Dr Govinda KC - Gregory G. Maskarinec; Madhusudan Subedi; Prativa Subedi; Arjun Karki (Social Medicine Publication Group, 2020)
At present, reforms of the critically flawed system of medical education in Nepal are urgently needed. The integrity of Nepal's medical education system is threatened by investors, including members of Nepal's parliament, political leaders, and influential businessmen who treat the creation of new for-profit medical schools as an easy way to generate profits quickly and effortlessly, while no effective, impartial central authority exists to regulate the situation. The pressure to approve new medical schools increases even when the resulting education may be substandard and debt-burdened graduates neither able to find post-graduate training opportunities nor willing to accept positions outside of the Kathmandu Valley. A major force driving efforts to reform, systematize, and improve medical education in Nepal is the series of ten non-violent fasts-unto-death campaigns of one dedicated physician, senior orthopedic surgeon Dr. Govinda KC. To put his efforts into historical context, we review medical education in Nepal from 1978, when Nepal's first medical school, the Institute of Medicine, was created. We seek to clarify whether the current trend toward for-profit medical education is compatible with the rule of law in Nepal, or whether Nepal risks becoming a failed state as it ignores the need to align the production of physicians with that of national health needs.